Peningkatan Kemampuan Guru Dalam Membuat Media Pembelajaran Menggunakan Aplikasi Berbasis Kecerdasan Buatan - Dyah Darma Andayani; Ridwansyah Ridwansyah; Gufran Darma Dirawan; Sitti Faika; Vilia Darma Paramita (Jurnal Sipakatau: Inovasi Pengabdian Masyarakat, 2024)
Pengabdian Masyarakat is implemented with the goal of introducing artificial intelligence-based applications to teachers who are expected to help them in developing learning media that will be used in the learning process of classes. The training was conducted for 5 days and followed by 72 teachers from high school level in Kabupaten Takalar. Model learning that is used is a combination of casebased learning and project-based learning. At the end of the implementation of the activity, the evaluation in the form of the questionnaire and the presentation is given untuk mengethait utamasiksi utilisan kegiatan. Overall, the training runs well and produces teachers who have been trained in using artificial intelligencebased applications.It can be seen that learning material that they create as their project has been made by using AI based application